Demystifying Fair Trade in France: The History of an Ambiguous Project - Özçağlar-Toulouse, Nil (Journal of business ethics, 2010)
In France, Fair Trade arrived on the scene in the late twentieth century, and since then has passed through several experimental phases before becoming an enduring “realistic” economic alternative. To understand the transformation, this article defines Fair Trade as a social construct issues and tensions of which change depending on the point of entry. By conducting a secondary analysis of several data sets from varied sources, including documentary material, interviews, and observations, the authors trace the history of Fair Trade in France, define its introduction as a system, describe its institutionalization, and contribute to a greater understanding of how its ideals have changed and become more professional over time. The analyses reveal that the term “Fair Trade” has become ambiguous, spanning divergent and conflicting ideas and projects, including opening and closing conventional market systems and alter-globalization and anti-globalization.